Volatility of Oil Prices - Wickham, Peter (Washington, D.C. : International Monetary Fund, 1996)
This paper examines the behavior of crude oil prices since 1980, and in particular the volatility of these prices. The empirical analysis covers 'spot' prices for one of the key internationally traded crudes, namely Dated Brent Blend. A GARCH (generalized autoregressive conditional heteroscedastic) model, which allows the conditional variance to be time-variant, is estimated for the period which includes the oil price slump of 1986 and the surge in prices in 1990 as a result of the Iraqi invasion of Kuwait. The paper also discusses the growth of futures and derivative markets and the dynamic links between spot and futures markets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet